The language/action approach to the design of computer-support for coorperative work a preliminary study in work mapping - Kensing, Finn; Winograd, Terry (1991)
Abstract: "Over the past few years, a methodology has been proposed by Flores, Winograd and their associates, for designing computer- based support systems and the reorganization that they can bring to cooperative work. This paper describes a study using an anthropologically based technique for systematic observation and interpretation of work flow, which relates this language/action perspective to the Scandinavian approach to systems development through participatory design. Our field study in an airport operations room has demonstrated the applicability of the theoretical framework and has clarified some practical issues in applying it to analyzing and redesigning work activities."
Keywords: System design